PENGUATAN KONSEP MAWAH DALAM USAHA PETERNAKAN SAPI DI AREAL KEBUN SAWIT - Noviar, Helmi; Syahril, Syahril; Badli, Saiful; Mardaleta, Mardaleta; Nasir, M. (Universitas Teuku Umar, 2025)
The mawah concept, a traditional form of profit-sharing cooperation, has long been rooted in the economic culture of Acehnese society. This system emphasizes mutual trust and equitable collaboration between livestock owners and caretakers, embodying values of solidarity and social justice. However, its practice is declining due to modern capitalist influences and a lack of institutional support. This community service project aimed to revitalize and strengthen the mawah system in the context of cattle farming within palm oil plantation areas in Teupin Panah Village, West Aceh. Utilizing methods such as field surveys, educational seminars, and interactive discussions, the project involved 35 local farmers and plantation workers. The program successfully introduced the mawah system as a fair and sharia-compliant model of economic cooperation, especially for community members with limited capital but agricultural expertise. Results indicated high participant engagement and a willingness to adopt the mawah system formally. The initiative highlights the potential of local wisdom to support sustainable community-based economic development through integrated livestock-plantation farming. Continued mentoring and institutional support are recommended to ensure long-term implementation and impact..